Project portfolio selection problem with exponential synergistic effects - Mohammadamin Hemmatizadeh; Emran Mohammadi (Journal of Project Management, 2019)
Project portfolio selection is a major issue in organizations, which involves a complex pro-cess from the first step to the end step of project selection. In order to pursue the organizations’ financial and physical constraints, choosing the most suitable portfolio of projects is necessary. Organizations have a number of constraints to select a portfolio of projects that must be considered. Different interactions are considered between the proposed projects. For example, resource constraints, the possibility of transferring liquidity resources that are not consumed over a period to the next, the interdependence between projects, and the synergistic impact of the projects are important. In this paper, an exponential function is considered for synergistic impact of the projects that make the problem more similar to the real-world problems. An illustrative example is used to demonstrate the appropriate application of the proposed model.